The Stakeholders’ Perception with Regard to the Implementation of XRecorder Application in Teaching English during Covid-19 Pandemic in One of Islamic School in Boyolali - Handayani, Duwi; Adityarini, Hepy; Prastiwi, Yeny (Budapest International Research and Critics University, 2021)
The outbreak of Covid-19 around the globe has affected all sectors, education is no exception. Those who works in education sector have to find a solution to contnuously providing education services while securing the health of the people involved. Thus optimalizing the use of technology for delivering materials for students who are studying from home is one of the solutions. In a similar vein, the implementation of technology is also highlighted in TPACK theory and Curriculum 2013. This study is aimed to describe the stakeholders’ perception with regard to the implementation of Xrecorder in teaching English in one of Islamic school in Boyolali. It adopted descriptive qualitative approach in which the teacher and the students were asked to provide their points of views on the implementation of application of Xrecorder in English lesson. The results showed that the stakeholder agree that the Xrecorder application bring benefits for students particularly for its user friendliness and low internet quota.